The Influence of Good Corporate Governance and Profitability on Sustainability Report Disclosure with Firm Size as A Moderating Variable (A Study Case on Banking Sector in Indonesia 2018-2023) - Listiani, Yunis; Fadjar, Achmad (Journal of Accounting and Finance Management, 2025)
This research aims to investigates the effect of the Independent Board of Commissioners, Audit Committee, and profitability on sustainability report disclosure in Indonesian banks, and whether firm size moderates these relationships. Using a quantitative approach with secondary data from 10 banks over the period 2018–2023, a total of 60 observations were analyzed using purposive sampling. Findings indicate that the Independent Board of Commissioners and profitability significantly and positively influence sustainability report disclosure, while the Audit Committee has no significant effect. Additionally, firm size moderates the effect of both the Independent Board of Commissioners and the Audit Committee, but not profitability, on disclosure. These results highlight the importance of governance and firm characteristics in enhancing sustainability transparency in the banking sector.